Two sides of the coin: Feedback-driven landscape formation results in trade-off between establishment and resilience of marram grass - Solveig Höfer; Lissie de Groot; Nathan Scanlan; Eva Lansu; Max Rietkerk; Martin Wassen; Tjisse van der Heide; Valérie C. Reijers (Oecologia, 2025)
Habitat-modifying plants engineer biogeomorphic landscapes through self-reinforcing interactions with their physical environment, or so-called ‘biogeomorphic feedbacks’. Nevertheless, benefits can vary across a biogeomorphic landscape gradient and between plant-life stages. For instance, European marram grass forms dunes by trapping sediments which triggers plant growth, in turn promoting sediment trapping. Yet, by increasing dune height and vegetation cover, marram grass mitigates sediment dynamics, inhibiting sediment-growth feedbacks, which ultimately leads to its demise. However, little is known about how dune formation affects the growth and survival of marram grass at different life stages. Therefore, we performed a two-level field experiment testing the effect of position on marram grass across the biogeomorphological dune gradient (beach, foredune, backdune) on (i) the establishment success of juvenile transplants and (ii) the resilience of mature plants to disturbance by above-ground biomass removal, over one growing season. Although juvenile transplants grew similarly well across the dune gradient, significantly fewer beach transplants (67%) survived compared to the foredune- and backdune transplants. Conversely, survival of mature disturbed marram grass (100%) was unaffected, yet recovery was highest at the beach and significantly decreased across the dune gradient. We could link these opposing responses to habitat modification. In heavily modified dune habitats sediment stabilization aided juvenile establishment, whereas the high sediment dynamics of unmodified beaches facilitated adult resilience indicating dune formation invokes a trade-off between establishment and resilience. Our findings highlight the importance of assessing life stage-dependent differences in environmental requirements of habitat-modifying plants to understand population dynamics and landscape-forming processes.

Delineation of the adult phenotype of Coffin–Siris syndrome in 35 individuals - Ariane Schmetz; Hermann-Josef Lüdecke; Harald Surowy; Sugirtahn Sivalingam; Ange-Line Bruel; Roseline Caumes; Perrine Charles; Nicolas Chatron; Krystyna Chrzanowska; Marta Codina-Solà; Cindy Colson; Ivon Cuscó; et al. (Human Genetics, 2024)

Genetic and phenotypic dissection of 1q43q44 microdeletion syndrome and neurodevelopmental phenotypes associated with mutations in ZBTB18 and HNRNPU - Christel Depienne; Caroline Nava; Boris Keren; Solveig Heide; Agnès Rastetter; Sandrine Passemard; Sandra Chantot-Bastaraud; Marie-Laure Moutard; Pankaj B. Agrawal; Grace VanNoy; Joan M. Stoler; David J. Amor; et al. (Human Genetics, 2017)